Perbandingan Kedudukan Anak Luar Kawin Menurut Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan dan Hukum Islam, Sikap Masyarakat Terhadap Anak Luar Kawin di Desa Lohayong, Kecamatan Solor Timur, Kabupaten Flores Timur - Yuyun Windasari Ratuloli; Yossie Maria Yulianti Jacob (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
This study aims to find out and analyze the comparison of the position of children out of wedlock according to law number 1 of 1974 concerning marriage and Islamic law, community attitudes towards children out of wedlock in Lohayong Village, East Solor District, East Flores Regency. This research is a normative judicial research using primary data obtained by conducting interviews, secondary data obtained from information sources in the form of the internet, books and other written notes. This study focuses on discussing the position of children out of wedlock according to law number 1 of 1974 concerning marriage and Islamic law and community attitudes towards children out of wedlock in Lohayong Village, East Solor District, East Flores Regency. The results of the study show that (1) Children out of wedlock in Law Number 1 of 1974 concerning Marriage are divided into two, namely legal children and children out of wedlock. The position of illegitimate children in the view of Islamic Law contained in the Compupulation of Islamic Law where an illegitimate child only has a civil or nasab relationship with his mother and his mother's family. (2) The attitude of the community towards children out of wedlock in Lohayong Village, East Solor District, East Flores Regency is known that the cause of children out of wedlock is due to religious differences, irresponsible couples and underage factors.